The Investigation of the Relationship between Real and Accrual Earnings Management and Capital Cost in Tehran Stock Exchange - Mohammadjavad zare bahnemiri (راهبرد مدیریت مالی, 2015)
Previous studies have shown that earnings management could have a significant effect on the company`s performance, particularly in the long run. Therefore, this effect may affect the company's cost of capital. As with the management earnings, the company's long-term performance reduces and consequently the cost of capital increases. The aim of this study was to investigate the relationship between accrual earnings management and real activities in 117 companies listed in Tehran Stock Exchange for a period of 7 years (2006 to 2012). In this study, the cost of capital was considered as the dependent variable and accruals earnings management and real activities were used as independent variables. The regression analysis was employed to test hypotheses and E_views software was used to analyze the data. The results indicate that there is a significant positive relationship between the accrual earnings management and real activities with the cost of capital.